PERANAN PEREMPUAN PEDAGANG HORTIKULTURA DALAM KELUARGA DI KECAMATAN MODOINDING - Fitia Karolina Tungka; Melsje Yellie Memah; Melissa Lady Gisela Tarore (Sam Ratulangi University, 2020)
This study aims to determine the extent of the role of women as wage earners in the family as horticulture traders in Modoinding Sub-District. This research was conducted in October 2019 until January 2020. The data used in this study are primary and secondary data. Sample selection method used the purposive sampling. Primary data collection was obtained through direct interviews using a questionnaire to 13 respondents, who are married, still have a husband and are a native of Modoinding. Secondary data were obtained from literature, official sources from related institutions, and other sources related to this research. Data analysis used the calculation of wife's income as horticultural traders, husband and children. The results showed that, the income of women horticultural traders could add to the economy in the family. The income earned by women horticultural traders per month is IDR. 1,500,000 - up to IDR. 5,500,000, - with work time per day from 8 hours to 17 hours. More income was generated from the wife's income as a trader with more time spent by the wife than the husband. So it can be said that the wife is the main breadwinner in the family. The research was 60% of children with income less than IDR. 2,000,000 - Income of more than IDR. 2,000,001 to IDR. 3,000,000 a month wass 20%, and income above IDR. 4,000,001 a month was 20%.*eprm*